Implementasi Dan Analisis Media Promosi Intren.Id Dalam Bentuk Motion Graphic - Alex Luxyendra; Afdhol Dzikri; Dimas Setiawan (Politeknik Negeri Batam, 2021)
Batampos.co.id is an online news portal that presents news about the Riau Islands, National, and International. But now the Batam post has given birth to a new online news portal that provides national news under the name intren.id. The implementation of Motion Graphic in intren.id promotion media aims to provide information in attractive packaging. The information that will be conveyed is about what is intren.id and introduces 4 categories in intren.id, namely news, lifetrend, entertainment, and travelogy by visualizing each category. The results of the analysis use the EPIC Model parameters, namely the dimensions of Empathy, Persuation, Impact, and Communocation. It is hoped that this motion graphic can convey information clearly, easily understood, and at the same time help the public, especially Batam, obtain reliable, quality, and quality information.